An Ergonomics study of Malaysian Multipurpose Smart Identity Card 'MYKAD' - Loo, Wee Hong (2008)
This research makes a groundbreaking contribution to the existing knowledge base as it is probably one of the first attempts to provide a holistic view on the use of smart NIC in a country acknowledged as the first in the world to implement such technology. This research is built upon the literature available on the UTAUT model where modifications were made. The findings do not merely benefit government, private sectors, practitioners, researchers but also provide great insights to other countries who are interested in or have implemented smart NIC.